Philopoesia: a poesia sonora de Philadelpho Menezes - Souza, Paulo Williams de (2024)
This work investigates the sound production of the poet and critic Philadelpho Menezes, as an experimental poetics of voice and performance, whose singularity is the key issue that we are interested in addressing, and for that, it is important to outline which strands of sound poetry Philopoetics engages with and how it metabolizes them into new compositions. The guiding hypothesis of the research is that the author's experimental sound poetry establishes a dialogical relationship with three trends of sound poetry: phonetism, electroacoustic effects, and the performative. The selection of the analysis corpus — “roof of the mouth”, “Poem, not-music” and “Sound poem for recital” —, found on the CD Sound Poetry: from phoneticism to contemporary poetics of the voice (1996), aimed to evaluate to what extent phonetism, electroacoustic effects, and performative elements, projected by the hypothesis, are explored in this triad, in order to enable the transfer to other sound poems of this Philopoetics. The research had theoretical foundations from authors such as Henri Chopin and Paul Zumthor, Enzo Minarelli, and Giorgio Agamben. The results obtained allow us to assert, from the analyzed poems, that the production of sound poetry by Philadelpho Menezes resides in border and paradigmatic systems, within intersemiotic fields